And God Created Laughter: The Eighth Day - Patella, Michael (Interpretation, 2015)
The subject of laughter does not surface often in the Bible, yet when we take Scripture in the fullness of the tradition, humor rises to the top. This article demonstrates that while laughter within the Bible often takes the form of cruel mockery, in the broad biblical landscape of faith laughter becomes a primary characteristic of the eschatological kingdom, ushered in by Christ’s resurrection—the Eighth Day. As people nourished by the Word of God, we must look to the Eighth Day in order to dwell in the Word’s fullness, and that fullness includes laughter.